Myocardial recovery with mechanical circulatory support. (14th June 2016) - Chaggar, Parminder S.; Williams, Simon G.; Yonan, Nizar; Fildes, James; Venkateswaran, Rajamiyer; Shaw, Steven M.
Abstract: Mechanical circulatory support (MCS) is instituted in patients with advanced heart failure, some of who may experience sufficient recovery in cardiac function to allow withdrawal of mechanical support. The incidence of left ventricular recovery with MCS is unclear as reported series in the literature demonstrate widely divergent rates. A number of clinical parameters (including echocardiographic, haemodynamic and physiological) are used to indicate likely left ventricular recovery during pump speed reduction but no internationally agreed definition exists. Withdrawal of MCS is not without risk and so robust clinical and biochemical definitions are important to minimize patient morbidity and mortality. Here we review our current understanding of left ventricular recovery with MCS.